The Twin Challenges for Tertiary Education in Low- and Middle-Income Countries - Bassett, Roberta; Geven, Koen (International Higher Education, 2025)
<h3 id="since-the-turn-of-the-twenty-first-century-tertiary-education-enrollments-have-exploded-globally-particularly-in-low–and-middle-income-countries-this-expanding-demand-for-tertiary-education-presents-two-central-challenges-for-policy-makers-managing-the-pressures-on-quality-relevance-governance-and-equitable-access-and-managing-the-financing-of-the-sector-effective-responses-will-involve-substantial-investments-in-infrastructure-training-diversification-of-delivery-and-regulatory-reforms" data-pm-slice="1 1 []">Since the turn of the twenty-first century, tertiary education enrollments have exploded globally, particularly in low- and middle-income countries. This expanding demand for tertiary education presents two central challenges for policy makers: managing the pressures on quality, relevance, governance, and equitable access; and managing the financing of the sector. Effective responses will involve substantial investments in infrastructure, training, diversification of delivery, and regulatory reforms.